Pancreatic dysfunction and its association with fat malabsorption in HIV infected children. Issue 4 (1st October 1998) - Carroccio, A; Fontana, M; Spagnuolo, M I; Zuin, G; Montalto, G; Canani, R B; Verghi, F; Di Martino, D; Bastoni, K; Buffardi, F; Guarino, A
Abstract : Background —Nutrient malabsorption frequently occurs in HIV infected children, but very few studies have investigated exocrine pancreatic digestive capacity in these cases. Aims —To investigate pancreatic function in HIV infected children and to determine whether faecal fat loss, a prominent feature of intestinal dysfunction, is associated with pancreatic dysfunction. Patients —Forty seven children with HIV infection without apparent pancreatic disease and 45 sex and age matched healthy controls. Methods —Pancreatic function was evaluated by measuring elastase 1 concentration and chymotrypsin activity in stools by ELISA and colorimetric methods, respectively. Intestinal function was evaluated by measuring fat and protein loss by the steatocrit method and by faecal α1 antitrypsin concentration. Results —14 (30%) had abnormal pancreatic function tests: seven had isolated elastase activity deficiency, three isolated chymotrypsin deficiency, and four pancreatic deficiencies in both enzymes. Patient enzyme values were significantly lower than those of controls. Low faecal pancreatic enzymes were not associated with symptoms. Twelve children had steatorrhoea and four had increased α1 antitrypsin. Steatorrhoea was significantly associated with reduced faecal pancreatic enzymes. There was a significant negative correlation between elastase 1 concentration and steatocrit. Children with pathological faecal elastase 1 or chymotrypsin values did not differ from the other HIV infected children with respect to nutritional and immunological status, stage of HIV disease, presence of opportunistic infections, or drug administration. Conclusions —Abnormal pancreatic function tests are a frequent feature of paediatric HIV infection; this condition is associated with steatorrhoea, which probably contributes to the disease.